PERAN SIKAP MEMEDIASI PENGARUH PEMASARAN HIJAU TERHADAP NIAT BELI PRODUK RAMAH LINGKUNGAN - Aprilisya, Ni Putu Eka; Kerti Yasa, Ni Nyoman; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen, 2017)
This research has purpose to determine the effect of the green marketing towards purchase intention, mediated by attitude. The research  did in Denpasar with 100 respondents as the sample. The population in this study was the consumers of Starbucks Coffee who never have or bought a Tumblr at Starbucks Coffee but know about it. The data analysis technique used was the technique of Path analysis and the Sobel test. The result indicated green marketing and also attitude had positive impact on the green product’s purchase intention in Denpasar. The variable of attitude was proved to be able mediated the effects of green marketing on green product’s purchase intention about the Starbucks’s Tumblr in Denpasar significantly. The implication of this research was the attitude had the important role in the green marketing that will impact on the green product’s purchase intention so that Starbucks Coffee expected to still promote its Tumblr
Keywords: Green Marketing, Attitude, Purchase Intention